(untitled) (Swiss Medical Weekly, 2011)
QUESTION UNDER STUDY: To investigate the aetiology and long-term clinical outcomes of patients diagnosed with digital ischemia. METHOD: Data of 36 consecutive patients presenting with digital ischemia were collected in July 2000 to June 2001 from a vascular referral centre. Demographic data, aetiology, medication and treatment were abstracted from the medical records. Clinical outcomes were assessed at 5 year follow-up including ulcer healing, digital amputation and mortality. RESULTS: Of the 36 patients, 69.4% were male and the mean age was 55 ± 14 years. In 15 patients (41.7%) a systemic disease was present and of those 53.3% was due to connective tissue disease. Twelve patients (33.3%) had hypothenar hammer syndrome and in 8 patients (22.2%) no apparent cause was found. Whereas 13 patients (36.1%) presented with rest pain or trophic lesions at baseline, no patients presented with these symptoms at follow-up. At follow-up, 18 (62.1%) patients had symptoms on provocation and 5 patients (4 patients with systemic disease and 1 with no apparent cause) had died. Digital amputation was performed in one patient at initial presentation and no digital amputation was performed at follow-up. No ulcer reoccurred and no workers’ insurance compensation was applied. Of those with hypothenar hammer syndrome, 80.0% had symptoms on provocation at follow-up. CONCLUSIONS: Among patients with digital ischemia, systemic disease and hypothenar hammer syndrome were the most frequent aetiologies. In patients with hypothenar hammer syndrome the clinical outcome was remarkably benign, although symptoms may persist with provocation, whereas patients with systemic disease have a high mortality rate.